The prognostic impact of lymphocyte subsets in newly diagnosed acute myeloid leukemia - Park, Yumi; Lim, Jinsook; Kim, Seonyoung; Song, Ikchan; Kwon, Kyechul; Koo, Sunhoe; Kim, Jimyung (Blood research, 2018)
Tumor-infiltrating lymphocytes, which form a part of the host immune system, affect the development and progression of cancer. This study investigated whether subsets of lymphocytes reflecting host-tumor immunologic interactions are related to the prognosis of patients with acute myeloid leukemia (AML). Lymphocyte subsets in the peripheral blood of 88 patients who were newly diagnosed with AML were analyzed by quantitative flow cytometry. The relationships of lymphocyte subsets with AML subtypes, genetic risk, and clinical courses were analyzed. The percentages of T and NK cells differed between patients with acute promyelocytic leukemia (APL) and those with AML with myelodysplasia-related changes. In non-APL, a high proportion of NK cells (>16.6%) was associated with a higher rate of death before remission ( =0.0438), whereas a low proportion of NK cells (≤9.4%) was associated with higher rates of adverse genetic abnormalities ( =0.0244) and relapse ( =0.0567). A multivariate analysis showed that the lymphocyte subsets were not independent predictors of survival. Lymphocyte subsets at diagnosis differ between patients with different specific subtypes of AML. A low proportion of NK cells is associated with adverse genetic abnormalities, whereas a high proportion is related to death before remission. However, the proportion of NK cells may not show independent correlations with survival.